Lot sizing and scheduling with sequence dependent setup costs and times and efficient rescheduling opportunities - Knut Haase; Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1996)
This paper deals with lot sizing and scheduling for a single-stage production System where setup costs and times are sequence dependent. A large bücket mixed integer programming (MIP) model is formulated which considers only efficient sequences. A tailor-made enumeration method of the branch-and-bound type solves problem instances optimally and efficiently. Furthermore, it will become clear that rescheduling can neatly be done.
Keywords: 650; Lot sizing; scheduling; production planning and control; rescheduling; sequence dependent setup times; Produktionssteuerung; Mathematische Optimierung; Theorie